2010
DOI: 10.1007/s12039-010-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Tungstate as a synergist to phosphonate-based formulation for corrosion control of carbon steel in nearly neutral aqueous environment

Abstract: Synergistic inhibition of corrosion of carbon steel in low chloride aqueous medium using tungstate as a synergist in combination with N,N-bis(phosphonomethyl) glycine (BPMG) and zinc ions is presented. The synergistic action of tungstate has been established through the present studies. The new ternary inhibitor formulation is effective in neutral and slightly acidic as well as slightly alkaline media. Potentiodynamic polarisation studies inferred that the formulation functions as a mixed inhibitor. Impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…[43][44][45] The fitting curves were also shown in Figure 3, and the parameters from fitting the EIS data and the corrosion inhibition efficiency (η) of Na 2 WO 4 are listed in Table IV. η values can be calculated by the following equation: 26,33 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[43][44][45] The fitting curves were also shown in Figure 3, and the parameters from fitting the EIS data and the corrosion inhibition efficiency (η) of Na 2 WO 4 are listed in Table IV. η values can be calculated by the following equation: 26,33 …”
Section: Resultsmentioning
confidence: 99%
“…26 The former peak corresponded to W 4f 5/2 , which shifted from characteristic elemental binding energy of 33.6 eV, and the latter peak corresponded to W 4f 7/2 electron, which shifted from 31.0 eV. 52 Such large shifts in the binding energy indicated that W existed in the +6 oxidation state (in the form of WO 3 ) in the surface film.…”
Section: Xps Analysis-mentioning
confidence: 99%
See 3 more Smart Citations